Antioxidants Maintain E-Cadherin Levels to Limit Drosophila Prohemocyte Differentiation - Gao, Hongjuan (Public Library of Science, 2014)
Mitochondrial reactive oxygen species (ROS) regulate a variety of biological processes by networking with signal transduction pathways to maintain homeostasis and support adaptation to stress. In this capacity, ROS have been shown to promote the differentiation of progenitor cells, including mammalian embryonic and hematopoietic stem cells and Drosophila hematopoietic progenitors (prohemocytes). However, many questions remain about how ROS alter the regulatory machinery to promote progenitor differentiation. Here, we provide evidence for the hypothesis that ROS reduce E-cadherin levels to promote Drosophila prohemocyte differentiation. Specifically, we show that knockdown of the antioxidants, Superoxide dismutatase 2 and Catalase reduce E-cadherin protein levels prior to the loss of Odd-skipped-expressing prohemocytes. Additionally, over-expression of E-cadherin limits prohemocyte differentiation resulting from paraquat-induced oxidative stress. Furthermore, two established targets of ROS, Enhancer of Polycomb and FOS, control the level of E-cadherin protein expression. Finally, we show that knockdown of either Superoxide dismutatase 2 or Catalase leads to an increase in the E-cadherin repressor, Serpent. As a result, antioxidants and targets of ROS can control E-cadherin protein levels, and over-expression of E-cadherin can ameliorate the prohemocyte response to oxidative stress. Collectively, these data strongly suggest that ROS promote differentiation by reducing E-cadherin levels. In mammalian systems, ROS promote embryonic stem cell differentiation, whereas E-cadherin blocks differentiation. However, it is not known if elevated ROS reduce E-cadherin to promote embryonic stem cell differentiation. Thus, our findings may have identified an important mechanism by which ROS promote stem/progenitor cell differentiation.